Distribution of floating marine macro-litter in relation to oceanographic characteristics in the Russian Arctic Seas; Marine Pollution Bulletin; Vol. 166 - Pogoeva M. Marina; Zhdanov I. Igor; Berezina A. Anfisa; Lapenkov A. Artem; Kosmach D. A. Denis; Osadchiev A. A. Aleksandr; Hanke G. Georg; Semiletov I. P. Igor Petrovich; Yakushev E. V. Evgeny (2021, 2021)
Title screen